Description and clustering of echolocation signals of Commerson's dolphins (Cephalorhynchus commersonii) in Bahía San Julián, Argentina - Reyes Reyes, María Vanesa (2015)
Commerson's dolphins (Cephalorhynchus commersonii) inhabit coastal waters of Southern South America and Kerguelen Islands. Limited information exists about the acoustic repertoire of this species in the wild. Here, echolocation signals from free-ranging Commerson's dolphins were recorded in Bahía San Julián, Argentina. Signal parameters were calculated and a cluster analysis was made on 3180 regular clicks. Three clusters were obtained based on peak frequency (129, 137, and 173 kHz) and 3 dB bandwidth (8, 6, and 5 kHz). The 428 buzz clicks were analyzed separately. They consisted of clicks emitted with a median inter-click interval of 3.5 ms, peak frequency at 131 kHz, 3 dB bandwidth of 9 kHz, 10 dB bandwidth of 18 kHz, and duration of 56 μs. Buzz clicks were significantly shorter and with a lower peak frequency and a broader bandwidth than most of the regular clicks. This study provided the first description of different echolocation signals, including on- and off-axis signals, recorded from Commerson's dolphins in the wild, most likely as a result of animals at several distances and orientations to the recording device. This information could be useful while doing passive acoustic monitoring.